1924
DOI: 10.1042/bj0181354
|View full text |Cite
|
Sign up to set email alerts
|

The Possible Significance of Hexosephosphoric Esters in Ossification

Abstract: PREVIOUS experiments [Robison, 1923], which demonstrated the presence of a phosphoric esterase in the bones of young animals, failed to detect this enzyme in unossified cartilage. The present work was undertaken to confirm this observation, and to determine whether any correlation could be traced between the appearance of the enzyme and the beginning of the ossification process in the cartilage. Our first experiments were carried out on the cartilages of a full-term infant who died 43 hours after birth. Extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1928
1928
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…However, the physiological concentrations of calcium and Pi [ 68 ] are not high enough to induce heterogeneous precipitation on collagen [ 6 ] or from solution [ 69 ]. In 1923, Robison [ 70 ] suggested that an enzymatically controlled Pi-concentration increase would be possible by cleaving “an organic ester of phosphoric acid.” One candidate enzyme for this activity in bone tissue is APase, which is associated with apatite biomineralization [ 71 ]. Geochemists and geomicrobiologists have similarly attributed inorganic and biological phosphorite precipitation to a discrete, local increase in Pi concentration.…”
Section: Mineral Saturation States and Nucleationmentioning
confidence: 99%
“…However, the physiological concentrations of calcium and Pi [ 68 ] are not high enough to induce heterogeneous precipitation on collagen [ 6 ] or from solution [ 69 ]. In 1923, Robison [ 70 ] suggested that an enzymatically controlled Pi-concentration increase would be possible by cleaving “an organic ester of phosphoric acid.” One candidate enzyme for this activity in bone tissue is APase, which is associated with apatite biomineralization [ 71 ]. Geochemists and geomicrobiologists have similarly attributed inorganic and biological phosphorite precipitation to a discrete, local increase in Pi concentration.…”
Section: Mineral Saturation States and Nucleationmentioning
confidence: 99%
“…Hexosephosphate is hydrolyzed by bone phosphatase (11). Liver phosphatase splits glycerophosphate, glucose-1 and glucose-6 phosphate at about the same rate (6).…”
mentioning
confidence: 99%
“…It is known that the alkaline phosphatase is a participating factor in bone formation (Martland & Robinson, 1924;Gomori, 1943 and others). This may take place on the removal of the inhibitor, pyrophosphate (Fleisch et al, 1966;Fourman & Royer, 1968).…”
Section: Discussionmentioning
confidence: 99%